2011
DOI: 10.1007/s13594-011-0023-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pure cheese snacks and expanded granule powders textured by the instant controlled pressure drop (DIC) process

Abstract: In this study, a new concept of pure cheese crispy snacks has been defined. The process used is the Détente Instantanée Contrôlée (DIC), for instant controlled pressure drop treatment, inserted between two air drying stages. Such cheese snacks can reach low water content (W<3 g H 2 O/100 g dry basis) and achieve high crispness level. A final simple grinding allows expanded granule cheese powders to be obtained. This paper investigates the impact of this process in terms of physical and structural properties su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…Our results are also in agreement with those recorded by Mounir et al () who reported similar tendency with a relative expansion ratio of 220–450% for various SD fruits and vegetables compared with AFD samples. Moreover, Mounir, Halle, and Allaf () found that the expansion ratio of SD snacks of pure cheese was up to 3,500% and Mounir, Besombes, et al () also proved an increase in specific surface area of SD apple by twice compared with AFD apple. Prachayawarakorn, Soponronnarit, Wetchacama, and Jaisut () found that the shrinkage of AFD shrimp was more visible than the superheated‐steam dried shrimp.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Our results are also in agreement with those recorded by Mounir et al () who reported similar tendency with a relative expansion ratio of 220–450% for various SD fruits and vegetables compared with AFD samples. Moreover, Mounir, Halle, and Allaf () found that the expansion ratio of SD snacks of pure cheese was up to 3,500% and Mounir, Besombes, et al () also proved an increase in specific surface area of SD apple by twice compared with AFD apple. Prachayawarakorn, Soponronnarit, Wetchacama, and Jaisut () found that the shrinkage of AFD shrimp was more visible than the superheated‐steam dried shrimp.…”
Section: Resultsmentioning
confidence: 94%
“…Swell drying is an alternative drying technique and discussed in many studies (Louka & Allaf, ; Mounir, ; Mounir, Allaf, Mujumdar, & Allaf, ; Mounir, Halle, & Allaf, ; Mounir, Téllez‐Pérez, Alonzo‐Macιas, & Allaf, ).The principle of swell drying is to perform instant controlled pressure drop technique (DIC) as a texturing step after a partial hot drying of the product. DIC is a high‐temperature short‐time treatment; T :up to 160°C and t : between some seconds and some dozens of seconds, followed by an instant dropping of pressure toward a vacuum ( ∼5 KPa) with a rate of Δ P /Δ t > 0.5 MPa s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…2009; Mounir et al . 2011; Chudy et al . 2019), but usually, full‐fat cheese was used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Expanded full-fat Cheddar was analysed by Rakcejeva et al (2009) using microwave vacuum drying. Instant controlled pressure drop processes were used by Mounir et al (2011) with Leerdammer cheese.…”
Section: Introductionmentioning
confidence: 99%